The antioxidant test, Ames' test and micronuclei test of chemical extract from White Kwao Krua Pueraria mirifica, Red Kwao Krua Butea superba, Black Kwao Krua Mucuna collettii and Kudzu Pueraria lobata - Wandee Sutjit (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2003